Study on progressive collapse resistance of single-layer reticulated shells. Issue 1 (February 2021) - Han, R; Yin, T Y; Yang, X D; Zhang, Y; Zhang, Y S; Ju, J S
Abstract: In order to analyze the progressive collapse resistance of single-layer reticulated shells, the finite element model of single-layer reticulated shell structure was established by ABAQUS software, and the method of removing key component constraints was used to simulate the progressive collapse resistance of the single-layer reticulated shell structure. The results show that the removal of the key components can cause the continuous failure of the upper members of the reticulated shell, and then lead to the progressive collapse of the whole structure.